“Benturan Asas Nemo Judex Idoneus In Propria Causa dan Asas Ius Curia Novit” (Telaah Yuridis Putusan Mahkamah Konstitusi Nomor 005/ Puu-Iv/2006) - Maladi, Yanis (Mahkamah Konstitusi Republik Indonesia, 2010)
Constitutional court as the guardian and the interpreter of the constitution has been providing solutions to address the constitutionality issues raised by the justices, the constitutional court in this case has done a comprehensive interpretation of the relevance of procedural law Nemo judex idoneus in propria causa in this case, which in the end use of the principle of constitutional court to answer Nemo in propria causa judex idoneus irrelevant to provide clarity of the constitutional issues raised.